Cardiac, Macro-, and Micro-Circulatory Abnormalities in Association With Individual Metabolic Syndrome Component: The Northern Shanghai Study - Zhao, Fang; Yang, Rong; Maimaitiaili, Rusitanmujiang; Tang, Jiamin; Zhao, Song; Xiong, Jing; Teliewubai, Jiadela; Chi, Chen; Blacher, Jacques; Li, Jue; Xu, Yawei; Jiang, Yan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study investigated the association of metabolic syndrome (MS) and its components with cardiac, macro-, and micro-circulatory abnormalities in an elderly Chinese population. Methods: This cross-sectional study was conducted using data for 1,958 participants from the Northern Shanghai Study aged over 65 years without a history of cardiovascular disease. MS was defined according to the National Cholesterol Education Program Adult Treatment Panel III in 2005 (NCEPIII 2005). Asymptomatic cardiovascular impairment parameters, including the left ventricle mass index (LVMI), peak transmitral pulsed Doppler velocity/early diastolic tissue Doppler velocity (E/Ea), carotid-femoral pulse wave velocity (cf-PWV), ankle-brachial index (ABI), carotid intima-media thickness (CIMT), arterial plaque, and urinary albumin–creatinine rate (UACR), were evaluated. Results: LVMI, E/Ea, cf-PWV, and the proportion of UACR > 30 mg/g exhibited increasing trends while ABI exhibited a decreasing trend according to the number of MS components (all p for trend < 0.01). Logistic regression analysis revealed that MS was significantly associated with LV hypertrophy (LVH), LV diastolic dysfunction, arteriosclerosis, and microalbuminuria (all p < 0.001). Central obesity and high blood pressure were associated with all cardiovascular abnormalities (all p < 0.05), whereas elevated plasma glucose was associated with arteriosclerosis and microalbuminuria (both p < 0.001). In addition, high triglyceride levels were associated with microalbuminuria (p < 0.05). Conclusions: MS is significantly associated with cardiac, macro-, and micro-circulatory abnormalities in elderly Chinese. Moreover, the presence of individual MS components may have specific prognostic significance.